PENGARUH PENDIDIKAN IBU DENGAN STATUS GIZI SISWA DI SMK BINA SEHAT NUSANTARA KABUPATEN BONE TAHUN 2022: THE EFFECT OF MOTHER'S EDUCATION ON THE NUTRITIONAL STATUS OF STUDENTS AT SMK BINA SEHAT NUSANTARA, DI KABUPATEN BONE TAHUN 2022 - Irwandi Rahmat (LPPM Institut Sains dan Kesehatan Bone, 2022)
Abstract. Balanced nutrition is a daily diet that contains nutrients in the type and amount according to the body's needs, namely gender, age and health status. Assessment of a person's nutrition is usually known as nutritional status. The success of a country to develop human resources is highly dependent on the nutritional status of its people. One of the factors that affect a person's nutritional status is people's knowledge of nutrition. One's knowledge can be seen from the level of education. This study aims to see whether there is an effect of the level of mother's education on the nutritional status of students who attend SMK Kesehatan Bina Sehat Nusantara Kabuapaten Bone. This research was conducted with analytical research method with a cross sectional approach. The research subjects were 33 students. Subjects who meet the criteria and are willing to take part in this study will fill out a questionnaire and their nutritional status will be measured through BMI (Body Mass Index). Furthermore, the data will be analyzed using Chi square analysis in the SPSS program. From the chi square analysis, it was found that there was no relationship between maternal education and the nutritional status of students at SMK Bina Sehat Nusantara, Kabupaten Bone. Abstrak. Gizi seimbang adalah susunan makanan sehari-hari yang mengandung zat gizi dalam jenis dan jumlah yang sesuai dengan kebutuhan tubuh yaitu jenis kelamin, umur dan status kesehatan. Penilaian terhadap gizi seseorang biasanya dikenal dengan status gizi. Keberhasilan suatu negara untuk mengembangkan sumber daya manusia sangat bergantung pada status gizi masyarakatnya. Salah satu faktor yang mempengaruhi status gizi seseorang adalah pengetahuan orang tentang gizi. Pengetahuan seseorang salahsatunta dapat dilihat dari tingkat pendidikanya. Penelitian ini bertujuan untuk melihat apakah ada pengaruh tingkat penidikan ibu dengan ststus gizi siswa yang bersekolah di SMK Kesehatan Bina Sehat Nusantara Bone. Penelitian ini dilakukan dengan metode penelitian analitik dengan pendekatan cross sectional. Subjek penelitian adalah pelajar sebanyak 33 orang. Subjek yang memenuhi kriteria dan bersedia mengikuti penelitian ini akan mengisi kuesioner dan akan di ukur status gizinya melalui IMT ( Indeks Massa Tubuh ). Selanjutnya data akan dianalisa menggunakan analisa Chi squere dalam program SPSS. Dari analisa chi squere, didapati tidak ada hubungan antara pendidikan ibu dengan status gizi siswa di SMK Bina Sehat Nusantara Kabupaten Bone.